Combined Effects of Inflammatory Status and Carotid Atherosclerosis: A 12-Year Follow-Up Study. Issue 12 (December 2016) - Mayer, Florian J.; Binder, Christoph J.; Wagner, Oswald F.; Schillinger, Martin; Minar, Erich; Mlekusch, Wolfgang; Tsiantoulas, Dimitris; Goliasch, Georg; Hoke, Matthias
Abstract : Background and Purpose—: Inflammatory responses play a key role in atherogenesis. The aim of this study was to assess the prognostic value of hsCRP (high-sensitivity C-reactive protein) and to evaluate whether degree of carotid stenosis and serum levels of hsCRP jointly predict long-term mortality in asymptomatic patients with carotid atherosclerosis. Methods—: One thousand sixty-five patients with neurological asymptomatic carotid atherosclerosis as evaluated by duplex sonography were prospectively followed for cause-specific mortality. Results—: During a median of 11.81 years, a total of 549 deaths, including 362 cardiovascular deaths, were recorded. The risk of all-cause and cardiovascular mortality significantly increased in patients with elevated serum levels of hsCRP (the adjusted hazard ratio for cardiovascular mortality per increase of 1 mg/dL of hsCRP levels was 1.47; P <0.001). Patients with a high degree of carotid stenosis and increased hsCRP levels were particularly at risk of adverse outcome. Patients with carotid narrowing over 50% and hsCRP levels >0.29 mg/dL (=median) had nearly twice as high a risk of cardiovascular mortality compared with patients with carotid stenosis of <50% and hsCRP levels <0.29 mg/dL (adjusted hazard ratio 1.89; P <0.001). Improvement in risk stratification with combined assessment of carotid stenosis and hsCRP was confirmed by an improvement of the continuous net reclassification improvement with 18% for all-cause mortality and 15% for cardiovascular mortality compared with the degree of carotid stenosis alone ( P <0.01). Conclusions—: Measurement of hsCRP in combination with ultrasound investigations of the carotid arteries at a single time point provides additional prognostic information for patients with asymptomatic carotid atherosclerosis. Abstract : Supplemental Digital Content is available in the text.